PENGARUH KOMPOSISI PEREKAT TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
One of the drawbacks of using particleboard bonded with urea formaldehyde (UF) is the formaldehyde emission, especially in a room with limited ventilation. Some countries have imposed restriction of allowable emission for certain uses.This work deals with the study on the effect of the use of variety of hardeners types and percentages of melamin formaldehyde (MF) as fortifier on formaldehyde emission. The experiment reveals that the effect of hardener mixed with catching agent and the effect of fortifier on formaldehyde emission was effective to curb down the formaldehyde emission.The effect of fortifier on some physical and mechanical properties was observed. It decreases water absorption and thickness swelling, increases shear strength; internal bond strength, and the modulus of rupture, but did not affect the modulus of elasticity.The effect of hardener mixed with catching agent on modulus of elasticity was not significant, while on other particle- board properties the effect was not consistent.